Reluctant partners: African Americans and the origins of the special relationship. (1st October 2016) - Webb, Clive
Abstract : This article assesses the overwhelmingly negative reaction of African Americans to the speech delivered by Winston Churchill in Fulton, Missouri, in March 1946. It shows that black intellectuals and activists fervently opposed the Anglo-American alliance championed by the former prime minister because they believed it a cynical attempt to buttress an exploitative overseas empire that Britain could no longer afford. African Americans considered Churchill a racist intent on preserving white global hegemony and suppressing the democratic aspirations of people of colour. Despite their initial optimism about the Attlee government elected to power in July 1945, they became almost as mistrustful of the Labour Party as they did the Conservatives. In demonstrating how African Americans considered the Anglo-American alliance to be a means of propagating white racism, the article provides a new perspective on grassroots resistance to the Special Relationship, emphasising tensions between diplomatic elites and ordinary citizens.